IdroGEO: A Collaborative Web Mapping Application Based on REST API Services and Open Data on Landslides and Floods in Italy - Iadanza, Carla; Trigila, Alessandro; Starace, Paolo; Dragoni, Alessio; Biondo, Tommaso; Roccisano, Marco (ISPRS international journal of geo-information, 2021)
The new national IdroGEO web platform allows the navigation, social sharing and download of data, maps, reports of the Italian Landslide Inventory, national hazard maps, and risk indicators. It is a tool for communication and dissemination of information to support decisions in risk mitigation policies, land use planning, preliminary design of infrastructures, prioritization of mitigation measures, management of civil protection emergencies, and environmental impact assessment. The challenges that have been faced during the design and development of the platform concern usability, access on multiple devices (smartphones, tablets, desktops), interoperability, transparency, reuse of information and software in the public sector, and improvement of the updating of the Italian Landslide Inventory. The methodologies and solutions adopted to address them include Progressive Web Application (PWA), Application Programming Interface (API), open standards, open libraries, and software. A landslide inventory management system has been developed via REST API for data entry and approval workflow in order to maintain the inventory in a distributed and collaborative manner. As a result, IdroGEO provides a public service for citizens, public administration, and professionals, using the “mobile first” approach and with scalable and reliable architecture. IdroGEO represents a solid infrastructure for the interoperability of data that serves as the foundation for creating a first knowledge-graph on landslides and the community who manages them.